Risk perception and knowledge of Human Papillomavirus infection among a group of Mexican males - Sosa-Hernandez, Diego (2024)
Introduction. Human papillomavirus infection is the most common sexually transmitted viral infection that might be prevented with knowledge and attitudes that promote safe sex. Males play a role in transmission as they are asymptomatic carriers of the virus, a situation that they ignore.  The aim of the study is to determine association between knowledge and risk perception with subclinical infection. Methodology. A prospective, cross-sectional and analytical study was conducted, including 164 males between 18 and 45 years, self-selected to be included. A self-administered instrument was used to measure perception of risk and knowledge about human papillomavirus infection with ten items using the Likert scale, five for measure risk perception and five to knowledge. Molecular biology, to identify the virus in the genitals, was used. Results. The male's average age was 29 years, with an infection prevalence of 24 %, 68 % of the population studied had a high perception of risk for acquiring the infection; 30 % medium risk, and only 2 % had a low perception. Regarding knowledge, 88 % had a high level and 12 % medium level. No association between knowledge level (p=0.53299) and perception of infection risk (p=0.53299) was found. Conclusion. No association between knowledge and risk perception with asymptomatic papillomavirus infection was found.